Innovative biosorption of crystal violet dye using chemically-enhanced pineapple crown leaf (CPCL) - Ni, Rabuyah; Hizami Rajiei, Muhammad Mirza; Paul, Rohit (Academica Press Solutions, 2025)
This study presents a sustainable and innovative approach to dye-contaminated wastewater treatment using pineapple crown leaves (PCL) as a low-cost biosorbent for the removal of crystal violet (CV) dye. Synthetic dyes like CV are widely used in the textile industry and pose serious environmental threats due to their toxicity, stability, and resistance to conventional treatment methods. Agricultural waste such as PCL offers an eco-friendly alternative for wastewater remediation, aligning with circular economic principles. In this work, raw PCL (RPCL) and NaOH-treated PCL (CPCL) were evaluated for their adsorption performance. Chemical treatment with sodium hydroxide significantly enhanced the surface properties of PCL by increasing porosity, surface area, and the number of active functional groups, as confirmed by Fourier Transform Infrared Spectroscopy (FTIR) analysis. Batch adsorption studies were conducted with varying adsorbent dosages to compare the dye removal efficiency of RPCL and CPCL. The results revealed that CPCL exhibited better adsorption capacity, achieving a maximum dye removal efficiency of 98.35%, compared to 97.02% for RPCL. The improved performance of CPCL demonstrates the effectiveness of alkali activation in enhancing biosorbent properties. This research emphasizes the potential of transforming agricultural waste into high-performance adsorbents for industrial wastewater treatment. The method is not only cost-effective and environmentally friendly but also scalable, offering practical applications in textile effluent management and rural water purification. The findings contribute to green chemistry initiatives and support sustainable innovation in environmental technology, making it highly relevant for industries seeking efficient, environmentally responsible dye remediation solutions.